Psychological Dynamics of Respectful Maternity Care: Provider–Patient Interactions in Rural Pakistan - Mushaim Gillani, Ijaz Battol, Amna Inayat (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Verbal and physical abuse, non-consented actions, ineffective communication, and emotional neglect are components of the disrespectful intrapartum care in Rural Pakistan. Such experiences not only increase psychological distress but also erode the trust in health care providers, compromising both mental health and service utilization. Objectives: The objectives are to examine the dynamics of provider and patient during childbirth in rural Pakistan, to qualify the frequency of treatment and its psychological impact on mothers, and to explore how treatment and psychological intervention contribute to respectful, emotionally supportive care. Material and Methods: This review includes the articles between 2020 and 2025; the search engines used were Google Scholar and PubMed. Results: Providing the intervention reduced the overall mistreatment by 50 percent and notably reduced verbal abuse and ineffective communication. S-RMC intervention reduced childbirth-related anxiety and depressive symptoms. After training, the staff reported an increase in empathy, communication, psychosocial awareness, and team coordination. In Karachi, postpartum anxiety was linked to sociocultural stress, lack of psychosocial support, and domestic responsibilities. Conclusion: Implementing theory-driven S‑RMC interventions in rural PHCUs effectively reduced mistreatment and promoted psychosocially supportive care. Provider empathy training and systemic accountability developed trust and psychological safety, significantly lowering the maternal anxiety and depressive symptoms. For sustainable progress, future strategies should integrate culturally sensitive, trauma-informed development, evaluation of long-term mental health impacts, and trauma-informed provider development. Keywords: Respectful Maternity Care, Psychosocial Support, Patient-Provider Relation, Postpartum Anxiety